Role of debinding to control mechanical properties of powder injection molded 316L stainless steel - ., Muhammad Rafi Raza, Faiz Ahmad, MA Omar, RM German, Ali S Muhsan (2013)
316L stainless steel is widely used in various industries due to low cost, ease of availability and exceptional combination of mechanical properties along with corrosion resistance as compared to the other available metal alloys. In powder injection molding, debinding is very critical step and improper debinding can change the final properties dramatically. In the present study, affects of debinding on mechanical properties of powder injection molded 316L stainless steel were studied.